Young Warsaw Adults of Convicted of Offences Bearing the Nature of Hooliganism (an ecological probe) (Archives of Criminology, 1972)
The principal aim of the article is to examine some aspects of the distribution over the area of Warsaw of offences committed by young adults (17-20 years) convicted of acts bearing the nature of hooliganism. The analysis of this question was based on material relating to young convicts resident in Warsaw who had sentenced for offences against the person or against public officials which were ruled by the courts to bear the nature of hooliganism. These young adults were inmates of Warsaw prisons in the years 1967 - 1968.In examining the criminal records of the 493 young adults serving sentences for hooligan offences account was taken of all their convictions between the ages  of 17 and 20, i.e. not the offences of a hooligan nature for which they were serving sentences at the time of the inquiry, but also their previous and subsequent convictions before they reached their 21st birthday.It was found that 45 per cent of them had more than one conviction between the ages of 17 and 20; of these recidivists 69 per cent had two convictions and 31 per cent three.It is also worth noting the fact that a third of all the young adults convicted of hooligan offences had, before their 17th birthday, appeared  in juvenile courts (usually on stealing charges). Of these 46.4 per cent had been prosecuted once, 16.1 per cent twice, and 37.5 per cent three or more times.  As regards the character of the offences of the 224 young adult convicts with more than one conviction since their 17th birthday, it was as follows:– 55 per cent of these recidivists had been convicted solely of  offences involving physical aggression (verbal aggression in only a few cases);– 40 per cent for offences involving aggression and at least one offence against property;– 5 per cent for offences involving aggression and other offences, but not against property;A study of the criminal records of these recidivists revealed that in as many as 73 per cent of these cases the offences were solely or chiefly ones of violence (there were only a very few instances of verbal aggression), a fact which merits special attention in view of the typical circumstance that these offences are generally committed while intoxicated.Only rarely, however, did the aggressive offences cause any more serious harm to the victims: among all the offences of this type, grave ones constituted no more than two per cent, or six per cent if robbery is included.Turning now to the ecological analysis of the law-breaking of the young adults convicted of hooligan offences, it should be remarked that the classification of Warsaw’s seven districts (boroughs) according to the incidence of the phenomenon in questions differs fundamentally depending on the frame of reference of the analysis: whether we make the criterion the place where the offence was committed or the place where the offender lives.In terms of the place where the hooligan offences of the young adult group in question were committed, the highest incidence rate was recorded in two districts: Central Warsaw and Northern Praga District. A similar picture emerged from a study of the police records relating to young adults suspected of offences against the person or public officials on the area of Warsaw. These two districts bear a resemblance to each other in certain respects: Central Warsaw is the commercial and entertainments centre of Warsaw, especially its left-bank neighbourhoods and Northern Praga performs the same role for right-bank Warsaw. Both these districts also contain railway stations serving the city’s environs. It is also worth emphasizing that both these districts also have the highest incidence of crime committed by all suspected male adults, not only aggressive offences, but other felonies in general. They also have the highest crime discovery rate.To sum up, it can be seen that the highest incidence of crime is to be found in the districts which are the commercial and entertainments centres of Warsaw.The classification of Warsaw’s districts is different when the factors taken into account relate to the place where the young adults convicted of hooligan offences lived and not where their offences were committed. The first two places are then occupied by Żoliborz and Mokotów, two districts with no specifically distinctive features (and basically of a residential nature). Central Warsaw, in first place as regards the incidence of hooligan offences, drops to last but one among Warsaw’s seven districts as the place of residence of the offenders.Since almost a half of the population in question were recidivists, the question arose whether there were any distinct variations in the percentage of recidivists resident in each district. It was found that a decidedly higher percentage of residents than the average for Warsaw as a whole was a feature of a traditionally industrial district (Wola).It seemed interesting to look into the relationship between the place of residence of the subjects and the place where they committed their offences. A majority of their offences were committed in the same district as they lived, with the percentage for each oscillating between 54.7 and 70.1. Central Warsaw stands out from other districts as one in which the majority of the offences committed within its area were committed by offenders resident elsewhere: only 36.8 per cent of those guilty of offences committed within its area also lived there, whereas the corresponding percentages for other districts run from 62 to 80 per cent.It was also found that each district contains certain neighbourhoods which are the homes of a particularly large number of young adults convicted of hooligan offences.Inquiries into the territorial distribution around Warsaw of various types of crime committed by different age groups are currently being conducted by the Department of Criminology of the Polish Academy of Sciences.